Introduction of artificial plants has no detrimental or beneficial effects on laboratory zebrafish husbandry but limits available swimming space - Aymene Youcef Krachni; Richard Busch; Indigo Brakus; Angelina Schumann; Jenny Wilzopolski; Nils Ohnesorge (PLoS ONE, 2026)
There is a broad consensus that husbandry conditions of laboratory animals need constant improvement to guarantee optimal animal welfare and research data quality. Zebrafish ( Danio rerio ) as one of the main animal models in biomedicine and toxicology are currently kept in barren tanks in most experimental setups, as well as in animal husbandry. Structural enrichment with artificial plants is discussed at the moment as a potential refinement measure to provide a more diverse environment. Other reports have shown that this can reduce stress or anxiety and improve cognitive abilities, survival rate and fertility in these animals. Still, concerns remain regarding its long-term benefits and drawbacks. Therefore, we introduced artificial plants in our husbandry tanks, and evaluated over a one-year period if in our specific system the benefits would outweigh the risks. When we compared pairwise 16 tanks that were either non-enriched or enriched with artificial plants, we saw no significant difference in terms of zebrafish survival rate during rearing, sex ratio, fertility or pathogen burden. When analyzing zebrafish behavior in their 8 L home-tanks, we saw statistically significant avoidance of the area close to the plants and a place preference for the open water in the middle or opposite side of the tank. This effect got more pronounced at lower holding densities. In summary, we found that introducing structural enrichment to our specific zebrafish facility carried low cost and no detrimental effects for the animals but a reduction of their free-swimming space. At the same time benefits were difficult to determine in our readouts as the survival rates of our fish were already very high without structural enrichment. We would like to encourage others to prepare similar forms of facility reports regarding enrichment to ensure a broader discussion on their potential long-term benefits in zebrafish husbandry systems.